2015
DOI: 10.5152/akd.2014.5380
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of single dose tadalafil in contrast-induced nephropathy: An experimental study

Abstract: Objective:Contrast-induced nephropathy (CIN) is one of the most common causes of acute renal failure in hospitalized patients. The direct toxic effect of contrast media; ischemic damage caused by reactive oxygen species; increased perivascular hydrostatic pressure; high viscosity and changes in the activity of vasoactive substances play important roles in the pathogenesis. Tadalafil inhibits the phosphodiesterase enzyme which destroys nitric oxide. Nitric oxide causes renal vasodilatation, increases renal medu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 30 publications
(32 reference statements)
6
21
0
Order By: Relevance
“…Özbek et al reported, in agreement with our results, that tadalafil exhibited a protective effect against kidney damage (25). This may be attributed to the cGMP/NO level that decreases during sepsis being protected by tadalafil.…”
Section: Discussionsupporting
confidence: 93%
“…Özbek et al reported, in agreement with our results, that tadalafil exhibited a protective effect against kidney damage (25). This may be attributed to the cGMP/NO level that decreases during sepsis being protected by tadalafil.…”
Section: Discussionsupporting
confidence: 93%
“…23 In addition, Ozbek et al showed that acute administration of tadalafil induced significant lowering of serum creatinine and blood urea nitrogen (BUN) values and also decreased serum and renal tissue malondialdehyde (MDA) levels, thus tadalafil protected rat kidney against contrastinduced nephropathy. 24 The hyperglycemia associated with diabetes can cause cellular changes in glomerular basement membrane and connective tissues supporting the capillary loops leading to glomerulosclerosis. 25 The histopathological findings validate these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Tadalafil increases the level of cGMP by blocking the enzyme phosphodiesterase-5, thereby increasing the level of nitric oxide and leading to vasodilation [26]. These findings may indicate the importance of the endothelium in the formation and inhibition of contrast nephropathy.…”
Section: Discussionmentioning
confidence: 96%